Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A V (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation

Datos sobre la flora y vegetación del Parque Natural de los Alcornocales (Cádiz-Málaga, España) - Pérez Latorre, A. V. (Acta botánica malacitana, 1999)
We have carried out a study about the flora, vegetation and landscape inthe Natural Park Los Alcornocales, located in the provinces of Cádiz and Málaga (SW of the Iberian Peninsula, Andalusia). The maximum altitude in the Park is 1091 m.; the dominant litology is characterised by sandstones and clays, in the NW prevail the limestones. The annual rainfalls are very abundant (between 800 and 1400 mm.) as well as the fogs regime, caused by the nearness to the Strait of Gibraltar; we have recognized two bioclimactic belts, thermo (annual mean temperature 17-18°C) and mesomediterranean (14-16°C) with accused oceanity. As a result, more than 1300 taxa of vascular plants have been catalogued, emphasizing in this work 77, because they are protected species, endemics or first records for western Andalusia; among them, 9 species are relictic ferns and have a great phytogeographic value. A total of 89 associations and communities have been inventoried. We have accomplished commentaries on sintaxa with a range superior to association. We lectotypified a subassociation and one association is neotypified. We describe as new sintaxa one order (Rhododendro pontici-Prunetalia lusitanicae), two alliances ldodendro ponticiPrunion lusitanicae and Salicion pedicellatae), 6 associations, 8 subassociations ad 1 combination. We have recognized 6 climactic series, among them one is new and characterised by forests of Quercus:broteroi on calcareous soils (Oleo sylvestris-Querceto broteroi S), other two are forests of Quercus suber on sandstones, another one is characterised by Quercus canariensis in wet slopes, one of Quercus pyrenaica in the summits and one of Quercus rotundifolia on lowland calcareous soils. As a mixed serie bound to the conditions of the vertisols occurs forests ofOlea sylvestris. As permanent vegetation on calcareous solis appears Ceratonia siliqua; on sandstones appears Junipertts oxycedrus; in summits flogged by strong winds we recognize a community with Quercus lusitanica and on rocky sandstones a relictual variant with Pinus pinaster. A mixed serie bound to the environmental humidity conditions as well as to wet soils is characterized by Rhododendron ponticum, similar to the macaronesian laurisilva. The series linked to rivers in the Park are characterised by: Alnus glutinosa (permanent stream rivers on sandstones), Salix pedicellata (partially droughted rivers), Populus alba (fluvisols), Fraxinus angustifolia (riverine sandyargilic soils), Nerium oleander (totally droughted rivers), Tarnarix africana (erratic or halophyll streams) and wet heaths with Erica ciliaris. Also exist communities mosaics bound to ecological corridors, human environments, rocks and cliffs, epiphytes, acrohalophylls and those tipycal of saline and aquatic environments. Finally, a commented syntaxonomic scheme, some inventories tables corresponding to the new or commented syntaxa and a map of the vegetation series of the Park are presented
Keywords: Andalucía; España; Flora; Los Alcornocales; Natural Park; sintaxonomy; Vegetation